Implementation of UAT and Blackbox Methods in the Android-Based Prayer Collection and News Portal Application of PP El-Bayan - Nur Moniroh; Rafiq Chasnan Habibi (Universitas Dinamika, 2025)
PP El-Bayan is a pesantren located in Cilacap. One of the books taught at this pesantren is Aurod, which contains a collection of prayers, poems, and guidelines for worship. Despite being in the digital age, PP El-Bayan does not yet have an application that includes Aurod and a pesantren news portal, so students are still required to bring the physical Aurod book in order to practice the prayers. This situation also indicates that the pesantren does not yet have a dedicated digital platform to share Islamic news and articles. This study employs the prototype method, which consists of six steps: first, gathering requirements and analyzing the existing system; second, quickly designing a model; third, creating a prototype; fourth, presenting the prototype; fifth, making revisions to the prototype if necessary based on feedback during the presentation and finally. The goal of this research is to develop an application that presents the prayers taught at PP El-Bayan and provides access to the latest news and Islamic articles related to the pesantren. This study resulted in the Bayanian application, an Android application containing a collection of prayers and news from Islamic boarding schools along with various additional features, which are expected to provide greater benefits to its users. The hypothesis of testing this material was accepted from the application with a user acceptance test, namely Good. with a result of 87.7%, so that the system is categorized as very strong according to Riduwan (2008), if the percentage results obtained reach 81% -100% then the test results can be said to be very strong so that the system that has been created can be implemented.